Ciudad fantasma - Coover, Robert (Serie Narrativa (Galaxia Gutenberg (Firm)), 2015)
A parody of the western novel featuring a hero who drifts into town to become both sheriff and outlaw. All the elements of the genre are present, from train robbery and runaway stagecoach, to cattle stampede.